2019
DOI: 10.1002/jtr.2264
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐border infrastructural development and residents' perceived tourism impacts: A case of China–Pakistan Economic Corridor

Abstract: Drawing on social exchange theory, Butler's tourism area life cycle model, and previous literature, this study empirically tests direct and indirect relationships among perceived impacts of China-Pakistan Economic Corridor (CPEC) infrastructural development, perceived tourism impacts, and support for tourism development. Using a sample of 800 questionnaires in structural equation modeling, the tested model explores that perceived impacts of CPEC infrastructural development as an antecedent, directly and indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 55 publications
(115 reference statements)
2
53
0
2
Order By: Relevance
“…The data (related to tables and figures) can be obtained on request from the ethics committee of NUST: anwar.msfin614@iiu.edu.pk. opportunities [14,19]. Second, our research provides some empirical evidence and contributes to the literature of CPEC, particularly in terms of rural development, infrastructure and the sustainable life of rural women.…”
Section: Plos Onementioning
confidence: 79%
See 2 more Smart Citations
“…The data (related to tables and figures) can be obtained on request from the ethics committee of NUST: anwar.msfin614@iiu.edu.pk. opportunities [14,19]. Second, our research provides some empirical evidence and contributes to the literature of CPEC, particularly in terms of rural development, infrastructure and the sustainable life of rural women.…”
Section: Plos Onementioning
confidence: 79%
“…Zakar, Zakar [ 17 ] reported that the non-availability of these opportunities further deteriorates their social status in the society and resultantly were less empowered [ 18 ]. The initiatives of the CPEC are expected to be useful in overcoming this social problem by enhancing their living standards through the provision of economic opportunities [ 14 , 19 ]. Second, our research provides some empirical evidence and contributes to the literature of CPEC, particularly in terms of rural development, infrastructure and the sustainable life of rural women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the local community can establish small businesses along with CPEC routes such as workshops, hotels, gas stations, and health centers (Ali et al, ). Regional connectivity provided by CPEC would also enhance the tourism industry in Pakistan (Nazneen, Xu, & Din, ), as Pakistan has beautiful landscapes that can also become lucrative ventures within the tourism and hospitality sector. According to prior entrepreneur literature, once an entrepreneur understands something as a viable business opportunity, it will assess the market opportunities to develop a viable business model (Kirzner, ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Recent findings revealed the positive effects of forest recreational activities in mental health and psychological and physiological wellbeing ("forest bathing") [25,26], which declares the need for the engagement and further development of forest recreation schemes and infrastructures. Tourism growth is highly dependent on infrastructures, such as the road network, transportation, accessibility amenities, and hotels, provided in the destination, while it is also appraised that infrastructural development influences local people in a positive way towards tourism development [27].…”
Section: Introductionmentioning
confidence: 99%